Optimization of a homogeneous ternary solvent system for the quantification of lead in crystal sugar samples - Chagas, Júnior Olair; Côrrea, Silviana; Melo, Isabela Cristina Silva; Lobo, Fabiana Aparecida; de Almeida, Alex Magalhães (Eclética Química, 2017)
During sugar production, contamination of the sugar by potentially toxic metals may occur. Therefore, it is necessary to develop methods to quantify these contaminants. An analytical method for the monitoring of lead in sugar samples was developed with the use of homogeneous ternary system of solvents and UV-Vis spectrophotometry. The ternary system was optimized using multivariate experiments and the best condition was: 10% water, 80% ethanol and 10% methyl isobutyl ketone. As the complexing agent, monosodium 4- (2-pyridylazo) resorcinol was used. The calibration curve was linear from 0.64 to 5.0 mg.L-1, ABS = 0.0873 [Pb2 +] - 0.0032 and R² = 0.9988. The limit of quantification was 0.53 mg.L-1 and limit of detection was 0.45 mg.L-1 with 95% confidence level, the standard addition curve was linear, ABS = 0.0736 [Pb2+] + 0.0846 And R² = 0.9971. Three samples were analyzed in triplicate and the concentration of lead obtained ranged from 84,741 ± 3,700 mg.Kg-1; 69.926 ± 11.837 mg.Kg-1 and 76.444 ± 7.1111 mg.Kg-1. For the standard addition curve, the concentration found was approximately 230,000 mg.kg-1. Considering the Brazilian standard, the lead concentration should not exceed 2.00 mg.Kg-1, thus, it is concluded that the values obtained were not within the norm for this metal.